Death in the margins - Gilbert, Victoria (Gilbert, Victoria. Blue Ridge library mystery, 2022)
It's early summer, and while Richard Muir and his dance partner, Karla, are preparing their new choreographic piece, Richard's wife, Amy, is gathering the dance's source materials. Based on folktales and the music of the Blue Ridge Mountains, the production is set to premiere at an old cinema that has been converted to a theater. But when dancer Meredith Fox Richard's former fiancé is found dead backstage, Amy is once again propelled into a murder case that threatens the careers and lives of those she loves. After Amy teams up with Chief Deputy Brad Tucker and the sheriff's department to discover the killer, they find that there's no shortage of suspects: Meredith's wealthy ex-husband, several fellow dancers, a romantically spurned accompanist, and others whom the talented but haughty dancer dismissed or betrayed over the years. With Richard and Karla's help, and information gleaned from locals who know a wealth of small-town secrets, Amy desperately tries to unveil the killer before the premiere. But she's pursuing a ruthless murderer who's willing to kill again and who might just be waiting for Amy in the wings.